Medicinal chemistry strategies towards the development of effective SARS-CoV-2 inhibitors - Shenghua Gao; Tianguang Huang; Letian Song; Shujing Xu; Yusen Cheng; Srinivasulu Cherukupalli; Dongwei Kang; Tong Zhao; Lin Sun; Jian Zhang; Peng Zhan; Xinyong Liu (Elsevier, 2022)
Novel therapies are urgently needed to improve global treatment of SARS-CoV-2 infection. Herein, we briefly provide a concise report on the medicinal chemistry strategies towards the development of effective SARS-CoV-2 inhibitors with representative examples in different strategies from the medicinal chemistry perspective.